Didymella fabae Punith.: mating type occurrence, distribution and phenotyping of the anamorph Ascochyta fabae Speg. in Tunisia - Omri Ben Youssef, Noura; Halila, Imen; Mbazia, Ahlem; Bessaidi, Zayneb; Missaoui, Khawla; Kharrat, Mohamed; Le May, Christophe (Frontiers in Plant Science, 2023)
Faba bean ascochyta blight, caused by Ascochyta fabae Speg. (teleomorph: Didymella fabae Punith.), is one of the most devastating diseases of the crop. It can cause yield losses that reach 95% in conducive weather conditions. Surveys were carried out in five regions of Tunisia: Beja, Bizerte, Jendouba, Kef and Tunis-Cap Bon. A total of 513 fungal isolates were collected from 2011 to 2013. A molecular characterization was conducted to identify the mating type of each individual using a mating type specific PCR. Results revealed that the two mating types MAT1-2 and MAT1-1 coexisted in all surveyed regions. An imbalance in favour of MAT1-2 was observed particularly in Bizerte and Jendouba regions (sex ratio was 18:85 and 32:80, respectively).Moreover, morphological and pathogenic characterization of 122 isolates among the collection revealed a significant variability in conidia type (one celled or two celled conidia) frequency, in conidia mean size and in aggressiveness toward Badii faba bean cultivar (incubation period, IP; percentage necrotic leaf area, S; and area under disease progression curve, AUDPC). A principal component analysis (PCA) performed on morphologically studied parameters (frequency of conidia cell number and conidia mean size) identified three groups of isolates based on morphological traits: one celled (1C) and two celled (2C) conidia rates, one celled and two celled conidia length and width (1L, 1W, 2L and 2W, respectively). A second PCA using aggressiveness parameters (IP: Incubation period, S1, S4 and S9: percentage of necrotic leaf area respectively 5, 20 and 45 days after inoculation) identified three distinct pathogenic groups: poorly pathogenic AG1, moderately pathogenic AG2 and highly pathogenic AG3. Morphological and pathogenic groups and mating type data were used to conduct a multiple factorial correspondence analysis (MFCA) which revealed a correlation between the variables studied. Five groups were identified, each associated with a morphological and pathogenic trait and mating type. The most pathogenic group belonged to MAT1-2 suggesting that in locations where MAT1-2 is prevalent the epidemic risk is more important.